Analisis Efektivitas Kerja dan Tata Ruang Kantor Karyawan PT. Pupuk Iskandar Muda - S Sutriani; H Hamdiah (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2022)
This study aims to analyzed the effectiveness of employee performance and lay out office at PT Pupuk Iskandar Muda. Sample obtained 15 respondents and conducted Deep Interview to the employee and staff in Human Resources Department. The results of data analysis show that if good lay out in the room of office it would be impact toincrease the effectivity of perpermonce of employee at PT. PUpuk ISkandar Muda. By considering the elements in the arrangement of office space, organizational goals can be achieved as expected.